Collaborative Governance Unit Pelaksana Teknis Perlindungan Perempuan dan Anak Dengan Lembaga Perlindungan Anak Dalam Menangani Kasus Kekerasan Anak di Provinsi Jawa Timur - Yulia Adinda Telussa; Dida Rahmadanik; M. Kendry Widiyanto (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
This study examines the implementation of Collaborative Governance between the Technical Implementation Unit for Women's and Children's Protection (UPT.PPA) and the Children's Protection Agency (LPA) in handling child abuse cases in East Java Province. With the high incidence of child abuse in this region, child protection has become an urgent priority. The aim of this research is to identify the forms of collaboration undertaken, the challenges faced, and the strategies to enhance the effectiveness of the collaboration. The findings indicate that the collaboration between UPT.PPA and LPA involves case referrals and joint handling that require mediation or special interventions by certified experts. Challenges include policy differences, limited resources and budgets, and uncertainties due to changes in government policies. This study recommends the drafting of a Memorandum of Understanding (MOU), strengthening resources and budgets, utilizing information technology to improve coordination, and public awareness campaigns on the importance of reporting child abuse cases. This research contributes to the understanding of the importance of structured collaboration and strategies to overcome obstacles in efforts to protect children from abuse.